Practical Aspects of Realisation of Negative Charge Pumps - Matoušek, David; Rejfek, Luboš (IEEE (Institute of Electrical and Electronics Engineers), 2017)
A charge pump is DC/DC converter that produces a higher output voltage than power supply or generates a negative output voltage. Some variants of charge pumps work as voltage regulator, too. A charge pump is realised by capacitors, transistors and/or diodes. Therefore, some charge pumps are integrated directly to the systems that use these charge pumps. E.g. Flash or EEPROM memories are supplied from standard voltage about 3 V, but write and erase processes use a greater voltage about 12 V. This paper is concentrated on comparison of standard variant of negative charge pump with a new design. Thus, the output voltage, rise time and other parameters of these negative charge pumps are compared by simulation executed by LTspice XVII. The simulated results are verified by practical realization of charge pumps in discrete form.
Praktické aspekty realizace negativních nábojových pump
Keywords: negative charge pump; Dickson charge pump; Fibonacci charge pump; series output resistance; negativní nábojová pumpa; Dickson nábojová pumpa; Fibonacci nábojová pumpa; sériový výstupní odpor